Intercropping for resilient and diversified agri-food systems in moisture-stress areas of Amhara - Teferi, Tesfaye Jorgi; Nega, Masresha Gashaw; Mersha, Tsedalu Jemberu (International Journal on Food, Agriculture and Natural Resources, 2025)
Intercropping is the practice of growing two or more crops together in the same piece of land, and at the same time-boosts yield stability, reduces risk, enhances food diversity, alleviates poverty, and strengthens climate resilience. This study evaluated sorghum-pulse intercropping effects on yield, food diversity, and land use efficiency under the moisture-deficit areas of Dengora and Kalay Gondar, Ethiopia, during the 2017-2018 cropping season. A randomized complete block design with nine treatments and three replications was used, including sole cropping of sorghum, green gram, and common bean, as well as intercropping systems (sorghum-green gram and sorghum-common bean) arranged in 1:1, 1:2, and 2:1 row ratios. The results showed that the maximum grain yield was obtained from both sole cropping treatments. All intercropping results showed that the land equivalent ratios were greater than one, indicating that intercropping is more efficient. The 1:1 sorghum-common bean intercropping system achieved the highest land equivalent ratio (1.4) and a significant intercropping advantage (4601-4837). Additionally, the 1:1 sorghum common-bean combination showed a 31% area time equivalent ratio advantage. Economic analysis revealed that the 1:1 sorghum common-bean arrangement yielded the highest net benefit (35,967 Ethiopian Birr). Based on agronomic performance and economic viability, the 1:1 sorghum common-bean intercropping system is recommended to enhance the resilience and diversification of the agri-food system in moisture-stress areas of Dengora and Kalay Gondar, Ethiopia, and similar agroecology.